2005
DOI: 10.1001/archinte.165.11.1267
|View full text |Cite
|
Sign up to set email alerts
|

Undertreatment of Obese Women Receiving Breast Cancer Chemotherapy

Abstract: Overweight and obese women with breast cancer often receive intentionally reduced doses of adjuvant chemotherapy. Administration of initial and overall full weight-based doses of adjuvant chemotherapy in overweight and obese women is likely to improve outcomes in this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
181
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(192 citation statements)
references
References 35 publications
3
181
0
8
Order By: Relevance
“…29 Obese women may be given lower doses of chemotherapy because the ideal body surface area rather than true body surface area is used to estimate the dose of chemotherapy. [30][31][32] The fact that obese women experienced less toxicity than normal weight women supports that hypothesis, but we did not detect an interaction between obesity and toxicity on breast cancer-specific survival. Other proposed biological mechanisms include higher estrogen levels among obese women that counter the efficacy of tamoxifen and increase cell proliferation, elevated adipokine levels caused by obesity that may accelerate cancer progression, independent effects of insulin, altered immune responses, and oxidative stress.…”
Section: Discussionmentioning
confidence: 56%
“…29 Obese women may be given lower doses of chemotherapy because the ideal body surface area rather than true body surface area is used to estimate the dose of chemotherapy. [30][31][32] The fact that obese women experienced less toxicity than normal weight women supports that hypothesis, but we did not detect an interaction between obesity and toxicity on breast cancer-specific survival. Other proposed biological mechanisms include higher estrogen levels among obese women that counter the efficacy of tamoxifen and increase cell proliferation, elevated adipokine levels caused by obesity that may accelerate cancer progression, independent effects of insulin, altered immune responses, and oxidative stress.…”
Section: Discussionmentioning
confidence: 56%
“…Obese postmenopausal breast cancer survivors have increased estrone, estradiol, free estradiol, levels and decreased sex-hormone-binding globulin levels [36]. Furthermore, it has been suggested that obese women with breast cancer may receive reduced doses of adjuvant chemotherapy [37]. Higher BMI has been related to more advanced stages of breast cancer at diagnosis in terms of tumour size [38].…”
Section: Biological Mechanismmentioning
confidence: 99%
“…The ASCO guidelines recommend that obese adult patients with cancer should be treated with chemotherapy doses based on ABW, especially when the goal of treatment is cure. No evidence shows that obese patients receiving chemotherapy would experience increased toxicity if actual weight were used to calculate the dose [13][14][15][16][17][18][19][20][21]. Clinicians should address treatment-related toxicities in obese patients in the same manner that they would for nonobese patients.…”
Section: Discussionmentioning
confidence: 99%